2023
DOI: 10.24875/gmm.m18000105
|View full text |Cite
|
Sign up to set email alerts
|

Frecuency of antigens and alloantibodies of Diego system in blood

Abstract: ResumenIntroducción: El sistema Diego es un sistema sanguíneo irregular involucrado de manera clínica en casos de enfermedad hemolítica del recién nacido y en reacciones postransfusionales, dentro de este sistema de han identificado a 22 antígenos eritrocitarios de los cuales el par Di a /Di b son los de mayor importancia por su potencial inmunogénico. Objetivo: Determinar la frecuencia del antígeno Di a y la identificación del aloanticuerpo en la población ecuatoriana. Métodos: Se realizó un muestreo aleatori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(12 reference statements)
0
1
0
Order By: Relevance
“… 14 Previous studies showed that the prevalence of the Di a antigen presents racial variation; in a study with blood donors in Ecuador, a 25% prevalence of the Di a antigen and an alloimmunization frequency of 6.09% against this antigen were found and a similar alloimmunization frequency was found in a Brazilian population study, which reported an anti-Di a alloantibody prevalence of 6.0% in 12,904 multi-transfused patients. 15 , 16 The presence of the Di a antigen in blood donors poses a risk to the Di a negative-transfused patients.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Previous studies showed that the prevalence of the Di a antigen presents racial variation; in a study with blood donors in Ecuador, a 25% prevalence of the Di a antigen and an alloimmunization frequency of 6.09% against this antigen were found and a similar alloimmunization frequency was found in a Brazilian population study, which reported an anti-Di a alloantibody prevalence of 6.0% in 12,904 multi-transfused patients. 15 , 16 The presence of the Di a antigen in blood donors poses a risk to the Di a negative-transfused patients.…”
Section: Discussionmentioning
confidence: 99%